1996
DOI: 10.1074/jbc.271.46.29060
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of the C-terminal Extension of Bovine αA-Crystallin Reduces Chaperone-like Activity

Abstract: ␣-Crystallins occur as multimeric complexes, which are able to suppress precipitation of unfolding proteins. Although the mechanism of this chaperone-like activity is unknown, the affinity of ␣-crystallin for aggregationprone proteins is probably based on hydrophobic interactions. ␣-Crystallins expose a considerable hydrophobic surface to solution, but nevertheless they are very stable and highly soluble. An explanation for this paradox may be that ␣-crystallin subunits have a polar and unstructured C-terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
111
0
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 60 publications
11
111
0
2
Order By: Relevance
“…The polar and flexible C-terminal tail is thought to promote the interaction of the chaperone with the hydrophobic region in the denatured protein and thus play a critical role in substrate-chaperone association. Indeed, previous reports indicated that the C-terminus of SNCG is particularly important in performing the protein binding and chaperone function (34,44). Consistent with the molecular modeling analysis, our studies using SNCG deletion mutants indicate that the C-terminal AA 106-127 is responsible for its specific binding to BubR1 and such binding is able to reduce the BubR1 interaction with Cdc20.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The polar and flexible C-terminal tail is thought to promote the interaction of the chaperone with the hydrophobic region in the denatured protein and thus play a critical role in substrate-chaperone association. Indeed, previous reports indicated that the C-terminus of SNCG is particularly important in performing the protein binding and chaperone function (34,44). Consistent with the molecular modeling analysis, our studies using SNCG deletion mutants indicate that the C-terminal AA 106-127 is responsible for its specific binding to BubR1 and such binding is able to reduce the BubR1 interaction with Cdc20.…”
Section: Discussionsupporting
confidence: 76%
“…A unique feature of chaperone proteins is a flexible hydrophilic tail region in the C-terminal. Nuclear magnetic resonance spectroscopy has revealed that proteins with chaperone-like activities have unstructured flexible solvent-exposed C-terminal extensions (44). The polar and flexible C-terminal tail is thought to promote the interaction of the chaperone with the hydrophobic region in the denatured protein and thus play a critical role in substrate-chaperone association.…”
Section: Discussionmentioning
confidence: 99%
“…5). There are good reasons to assume that charged and otherwise polar residues in this extension are important to pro- vide the solubilizing power to keep the complex of sHsp and unfolding substrates in solution [23,30]. Although Hsp20 has a flexible C-terminal extension similar in length to that of ABcrystallin, this is apparently not sufficient in itself for an optimal chaperone capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Samples containing reconstituted recombinant Hsp20 and AB-crystallin were diluted with phosphate buffer (0.1 M Na 2 SO 4 , 20 mM NaP i , pH 6.9) to concentrations ranging from 100Ϫ300 µg/ml and scattering was measured as a function of the temperature, essentially as described previously [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation